Rotman Lens Size Reduction by Using Same-Size Double Rectangular Defected Ground Structures (DGSs) Method or Same-Size Double Rectangular Slots Method - Rizky Hidayat Prasetyo; Eko Tjipto Rahardjo (Journal of Robotics, Automation, and Electronics Engineering, 2024)
The need for dedicated communication keeps increasing. A technique to realize that is by using multibeam radiation. A Beamforming Network (BFN) is required to enable multibeam capability in array antennas. This study uses the Rotman Lens as BFN in the frequency of S-Band. The common problem with using Rotman Lens is that its conventional design size is quite large, mainly due to its transition leg ports. Transition leg ports are important to ensure the matching impedance between the lens and the array antenna ports the lens and the beam ports or the lens and the dummy port. The goal of this study is to reduce the size of Rotman lens transition legs by implementing simple and uniform size of slots or Defected Ground Structures (DGSs) methods for the ports of the Rotman Lens BFN. The method can minimize the length of the transition leg and allow the BFN to operate efficiently. The results revealed that the use of the same double-rectangular DGS technique and the same double-rectangular slots in ports can reduce the size of the Rotman lens. Compared to the conventional methods, the proposed method can reduce the size to almost 85 percent from its original size for this S-Band implementation. The other performances of the BFN, besides the size reduction, are not degraded by implementing the proposed methods.